If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4log(5x + -3) = 8 Reorder the terms: 4glo(-3 + 5x) = 8 (-3 * 4glo + 5x * 4glo) = 8 (-12glo + 20glox) = 8 Solving -12glo + 20glox = 8 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -8 + -12glo + 20glox = 8 + -8 Combine like terms: 8 + -8 = 0 -8 + -12glo + 20glox = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-2 + -3glo + 5glox) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-2 + -3glo + 5glox)' equal to zero and attempt to solve: Simplifying -2 + -3glo + 5glox = 0 Solving -2 + -3glo + 5glox = 0 Move all terms containing g to the left, all other terms to the right. Add '2' to each side of the equation. -2 + -3glo + 2 + 5glox = 0 + 2 Reorder the terms: -2 + 2 + -3glo + 5glox = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3glo + 5glox = 0 + 2 -3glo + 5glox = 0 + 2 Combine like terms: 0 + 2 = 2 -3glo + 5glox = 2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (8*x^3)+(6*x)=3 | | 13y-6y=14 | | 10y/-3=-15 | | 4ln(5x-3)=8 | | 3x-47+97=180 | | 25=15x+1.25 | | 7d-5+4d= | | 3x-47=180 | | 122-73= | | 2-2/5x=1/5x-4 | | 3j+5t=17 | | (8x+1)(x-2)=13-x | | x/-14=-40 | | 6x-4yi+2i=6-ix-yi | | (8x+1)(x+2)=13-x | | (-6m-sqrt(36m^2-4m))/2 | | 8(b+1)+4=3(2b-3)-16 | | 10x-1-7x=35 | | 13*a-4-3=65 | | 61+b= | | 3x+1-x+2= | | 4d-10d=54 | | 6+4c=-26 | | 12-(x+7)=6x-2 | | 3x+16=x-4 | | 6(x-1)=18-2(3-2x) | | 275=21-w | | 0.25x+8=22 | | 2x-5(x-4)=1-4x | | 12.5x+15=-3.75 | | 4.44+4x-4=311.11-x-7 | | 4w-16=32 |